A clinical activation protocol improves response time to urgent/emergent neurosurgical care in children with brain tumors and intracranial hemorrhage - Rishi Jain; Hinda Najem; Shreya Mukherjee; Megan Votoupal; Kaethe Leonard; Julia Martorana; Yiannis Katsogridakis; Michael DeCuypere (Child's Nervous System, 2026)
Abstract Introduction While there are well-established protocols for trauma and ischemic stroke care, there are few dedicated to brain tumors or non-traumatic intracranial hemorrhage (ICH), especially within pediatric neurosurgery. At Ann & Robert H. Lurie Children’s Hospital of Chicago, a neurosurgical emergency activation protocol for non-traumatic intracranial emergencies, Code Intracranial Emergency (CIE), was developed and applied in 2021. This is a multidisciplinary protocol with synchronized workflows, predetermined roles, scripted communication, and streamlined patient assessment. Here we examine the effectiveness of this protocol in time management and access to care at a large tertiary referral center. Methods Sixty-four patients with either a brain tumor or a non-traumatic ICH were retrospectively reviewed. We utilized a case–control study design for comparison purposes (January 2016–August 2022 [no code deployed, control cases, n = 36]; September 2021–January 2023 [CIE deployed, n = 28]). Both cohorts were matched for age and diagnosis/pathology. Group comparisons were conducted across time intervals (time from the emergency department (ED) to initial imaging, time to initial neurosurgery consultation, time to operating room (OR) arrival, and total length of hospital stay). Results Across all tumor patients, the protocol significantly reduced the time from consultation to OR arrival ( p = 0.03). For urgent/emergent tumor-related cases, significant improvements were observed in consultation to OR arrival time ( p < 0.01). In addition, protocol utilization led to a significant reduction in consultation to OR time ( p = 0.024) and lowered average ED to initial imaging time (56 min vs. 1.19 h) for urgent ICH cases. Conclusions Implementation of CIE effectively reduced response time to OR arrival for patients suffering from intracranial tumor and ICH emergencies. While this cohort is underpowered, this analysis highlights the importance of a multidisciplinary protocol for optimal workflow during neurosurgical emergencies, where timely and streamlined communication is crucial for effective access to care.